Effect of salt concentration in aqueous LiTFSI electrolytes on the performance of carbon-based electrochemical capacitors. (1st September 2021) - Pameté Yambou, E.; Beguin, F.
Abstract: Herein, appropriate electrochemical methods are used to determine precisely the electrochemical stability window (ESW) of carbon electrodes and cell potential of electrical double-layer capacitors (EDLCs) when using aqueous solutions of LiTFSI at concentrations ranging from 1 to 20 mol kg −1 . We show particularly that, due to the low hydration degree of the Li + cations in the 20 mol kg −1 LiTFSI solution, and consequently lower amount of water available in the electrical double-layer, hydrogen chemisorption is dramatically reduced under negative polarization of a porous carbon electrode, as compared to the 1 mol kg −1 and 7 mol kg −1 LiTFSI solutions. At the positive AC electrode, the oxygen evolution potential is pushed to higher values with increasing the LITFSI concentration and it results in an extension of the ESW from 1.6 V to 1.8 V and 2.0 V in 1 mol kg −1 LiTFSI, 7 mol kg −1 LiTFSI and 20 mol kg −1 LiTFSI, respectively. However, in the case of an EDLC with positive and negative carbon electrodes of equal mass in 20 mol kg −1 water-in-LiTFSI electrolyte, the maximum cell potential under floating conditions is only 1.8 V. The lower capacitance of the negative electrode (C-  = 91 F g   −   1 ) than the positive one ( C + = 122 F g   −   1 ) during galvanostatic cycling up to 1.6 V suggests different mechanisms of EDL formation. TG-MS analyses on electrodes extracted from a cell in 20 mol kg −1 LiTFSI after potentiostatic floating at 1.6 V prove that the TFSI − anions are trapped in the porosity of carbon whatever the polarity. Bulky solvated and at least partially desolvated Li + cations are permselectively adsorbed in the negative electrode when using the 20 mol kg −1 and 1 mol kg −1 LiTFSI aqueous media, respectively, whereas ion-exchange (removal of Li + cations and replacement by TFSI − anions) is the dominant mechanism at the positive electrode in both media.